ANANLISIS IMPLEMENTASI JOB DESCRIBTION SEBAGAI UPAYA MENINGKATKAN KINERJA KARYAWAN - Dewi Mudawamah; Andriani Andriani (CV. KAMPUSA AKADEMIK PUBLISHING, 2025)
This research aims to analyze the practice of implementing job descriptions and their contribution to employee performance at PT. Jatinom Indah Agri. Based on the phenomena found, companies operating in the chicken feed sector do not yet have clear and specific job description documents, although verbal communication regarding duties has been implemented. The research method used is descriptive qualitative, with data collection through interviews and observation. The research results show that even though the job description is informal, employees can understand their duties and responsibilities, which has a positive impact on performance. However, lack of documentation leads to misunderstandings and overlapping responsibilities, which hinders coordination between divisions. Therefore, it is important for PT. Jatinom Indah Agri to document job descriptions systematically and up to date to increase work efficiency and achieve company goals. This research underlines the importance of good human resource management through the application of job descriptions as a tool to control and limit employee performance.